Evaluating the Service Delivery of IRRI-STRASA Project for Disseminating Improved Rice Varieties in Nepal - Baral, Prakash; Paudel, Rajesh; Pandey, Laxmi; Gyawali, Binam; Khadka, Alisha (Journal of Agriculture and Forestry University, 2025)
STRASA project is the joint venture of IRRI-IAAS focusing in disseminating improved and tolerant rice varieties suitable to local conditions. A study was carried out to evaluate the extension service delivery of the project in two municipalities namely Bhanu, and Sundarbazar, selecting 101 sample households. Survey design with structured questionnaire, Focus Group Discussion and direct observation were used for data collection under pragmatic paradigm. The study showed that the average participation of respondents in project was 6.14 years, which had significant impact on their economic yield, production cost, food sufficiency and social networks. Majority of respondents were in frequent contact with extension personnel (fortnightly and monthly) and perceived that the services were credible, applicable, relevant and timely delivered with cost efficiency of 0.62 implying that the project was cost efficient in study areas. The technical competency and managerial skills were acquired by respondents highly through project, with decision making and social mobilization levels of women participation significantly increasing after project intervention. The disseminated varieties were highly adopted while post-harvest techniques were least adopted. As only 9% respondents were dissatisfied and remaining respondents had positive attitude towards project activities, the service delivery could be deemed effective and impressive in study areas.